Ras activation of genes: Mob-1 as a model. - Liang, P (1994)
The ras oncogenes function by indirectly controlling expression of a subset of yet-undefined genes that are crucial for cell growth and differentiation. In a differential display strategy, numerous genes were identified on the basis of their differential expression in rat embryo fibroblasts transformed by the cooperation of mutant Ha-ras and p53 genes. We demonstrate here that one such gene, designated mob-1, is a downstream target of the Ras signaling pathway. The 417-bp mob-1 promoter, which contains dual NF-kappa B and AP-1 binding sites, confers the Ras inducibility. Oncogenic Ras as well as serum growth factors that activate endogenous Ras can induce mob-1 expression, but with a fundamental difference in that the oncogenic induction is constitutive whereas the serum induction is transient. mob-1 encodes a small secretory protein with a high degree of homology to IP-10, a member of a proinflammatory cytokine family. These findings link chronic inflammatory response to constitutive ras activation and tumorigenesis. Mob-1 may serve as a secreted marker for oncogenic Ha-ras mutations.